Patient-Level Factors Influencing Palliative Care Consultation at a Safety-Net Urban Hospital. (November 2021) - Nguyen, Minh-Thuy; Feeney, Timothy; Kim, Chanmin; Drake, F. Thurston; Mitchell, Suzanne E.; Bednarczyk, Magdalena; Sanchez, Sabrina E.
The influence of patient-level factors on palliative and hospice care is unclear. We conducted a retrospective review of 2321 patients aged ≥18 that died within 6 months of admission to our institution between 2012 and 2017. Patients were included for analysis if their chart was complete, their length of stay was ≥48 hours, and if based on their diagnoses, they would have benefited from palliative care consultation (PCC). Bayesian regression with a weakly informative prior was used to find the odds ratio (OR) and 99% credible interval (CrI) of receiving PCC based on race/ethnicity, education, language, insurance status, and income. 730 patients fit our inclusion criteria and 30% (n = 211) received PCC. The OR of receiving PCC was 1.26 (99% CrI, 0.73-2.12) for Blacks, 0.81 (99% CrI, 0.31-1.86) for Hispanics, and 0.69 (99% CrI, 0.19-2.46) for other minorities. Less than high school education was associated with greater odds of PCC (OR 2.28, 99% CrI, 1.09-4.93) compared to no schooling. Compared to English speakers, non-English speakers had higher odds of receiving PCC when cared for by medical services (OR 3.01 [99% CrI, 1.44-5.32]) but lower odds of PCC when cared for by surgical services (0.22 [99% CrI, <0.01-3.42]). Insurance status and income were not associated with differences in PCC. At our institution, we found no evidence of racial/ethnic, insurance, or income status affecting PCC while primary language spoken and educational status did. Further investigation is warranted to examine the system and provider-level factors influencing PCC's low utilization by medical and surgical specialties.